Minority Rights, Freedom of Religion and the Issue of Burqa - Sanath Wijesundara (Politeknik Negeri Bali, 2019)
General stance of the Human Rights discourse is that minorities are subjected to discriminations, they are treated as second class citizens by the majority, and, hence, their rights are specially to be protected. Religious minorities encounter typical problems in practicing and observing their religions and cultures. Religious minorities in European countries in which secular and liberal democratic form of governments are in place enjoy their rights comparatively better is a fact not much contested. However, the burqa ban in France in 2010 followed by Belgium and many other European countries provides a testing field of religious minority rights and religious freedom under secular and liberal democratic states. This essay tries to explore how two of the founding stones of Human Rights discourse namely equality and non-discrimination are protected or breached with the ban of burqa. Views pro and against are evaluated on the basis of various theories and concepts. UN declarations and conventions as well as European conventions were readily consulted for authorization, verification and validation of facts. ECtHR’s remarks on the validity of the ban are tested against human rights discourse, equality and non-discrimination in particular. The essay opens an avenue for discussion of different views about the ban from different perspectives. Key Words: Religious minority, substantive equality, non-discrimination, public good & safety, tolerance, reciprocity, pluralism.